Favorite Fairy Tales : Find the hidden object in each fairytale - Arnsteen, Katy Keck (U.S.A : Derrydale books, 1990)
A discovery book featuring fairy tales and hidden cluesfor the reader to find it
Keywords: Fairy tales; Folklore